Protein Engineering Techniques Gateways to Synthetic Protein Universe - Poluri, Krishna Mohan; Gulati, Khushboo (SpringerBriefs in Forensic and Medical Bioinformatics,, 2017)
This brief provides a broad overview of protein-engineering research, offering a glimpse of the most common experimental methods. It also presents various computational programs with applications that are widely used in directed evolution, computational and de novo protein design. Further, it sheds light on the advantages and pitfalls of existing methodologies and future perspectives of protein engineering techniques.